Quantitative Detection of Chicken and Turkey Contamination in Cooked Meat Products by ELISA. (23rd November 2019) - Thienes, Cortlandt P; Masiri, Jongkit; Benoit, Lora A; Barrios-Lopez, Brianda; Samuel, Santosh A; Meshgi, Mahzad A; Cox, David P; Dobritsa, Anatoly P; Nadala, Cesar; Samadpour, Mansour
Abstract: Background : Concerns about the contamination of meat products with undeclared meats and new regulations for the declaration of meat adulterants have established the need for a rapid test to detect chicken and turkey adulteration. Objective : To address this need, Microbiologique, Inc. has developed an ELISA that can quantify the presence of chicken and turkey down to 0.1% (w/w) in cooked pork, horse, beef, goat, and lamb meats. Results : This chicken/turkey authentication ELISA has an analytical sensitivity of 0.000037% and 0.000048% (w/v) for cooked andautoclaved chicken, respectively, and an analyticalrange of quantitation of 0.025–2% (w/v), in the absence of other meats. The assay cross-reacts with cooked duck and pheasant but does not demonstrate any cross-reactivity with cooked pork, horse, beef, goat, and lamb meats, egg, or common food matrixes. Conclusions : The assay is rapid, can be completed in 70 min, and can detect a 0.1% level of meat adulteration. Highlights : The Microbiologique Cooked Chicken/TurkeyELISA can quantitate cooked chicken/turkey in the presence of pork, horse, chicken, goat, or sheep meat to 0.1% (w/w) and is not affected by common food matrixes.